Globalization, Work Intensification and Work-life Balance - Nakra, Rashmi (Ushus Journal of Business Management, 2005)
The performance and change challenges experienced by organizations in the global village are unprecedented and there is every reason to believe that these will continue to grow. In the incessant quest for higher performance, the pressures felt by organizations are being deflected on to their employees. This has resulted in a profound change in the employment relationship, making it more transitory and flexible. This paper looks at the impact of globalization on the employment relationship and work intensification. The results based on a sample of 77 employees from 34 private sector organizations indicate that work intensification is prevailing at significant levels. These findings suggest that it is time for a rigorous empirical look at work intensification and work-life balance. Finally, the managerial implications of the suggestions made by the respondents for moderating the work intensification are discussed.